Unveiling the Online Presence: A Comparative Study of Social Media Use in Branding Creative Cities - A Case Study of Singapore and Bandung - Prayudi Prayudi; Kartika Ayu Ardhanariswari; Ninik Probosari (Jurnal Ilmu Komunikasi, 2024)
This article compares the social media strategies and engagement metrics utilized by two prominent creative cities, Singapore and Bandung. Singapore and Bandung are creative cities using different social media techniques and measurements. This research examined how the Singapore Design Council and Bandung Creative City Forum used social media to brand their cities. This research further analyzes social media in terms of reach and sentiment. The study adopted descriptive and social media analyses. The purpose was to obtain social media strategies and compare their social media channels, mentions, reach, and sentiment. The research findings show that Singapore's leading creative city branding platform is Instagram, proposing a more focused strategy. Bandung communicates with its numerous online citizens via Instagram and Twitter. Bandung generates more social media mentions and reaches, indicating a more active and engaged online community. Despite this, Singapore's social media sentiment is overwhelmingly positive, reflecting a solid and favorable perception of the city as a creative center. In addition, the study emphasizes the significance of platform selection and content diversity when developing social media strategies. This comparative analysis contributes to a comprehension of the effective use of social media for creative city branding. The study informs stakeholders in Singapore and Bandung about the strengths, limitations, and opportunities of their social media engagement. By utilizing these findings, policymakers, urban planners, and creative industry professionals can enhance their efforts to promote their cities as thriving creative centers.